TUKANG SUUN ANAK-ANAK : BENTUK EKSPLOITASI ORANGTUA TERHADAP ANAK (Studi Kasus di Pasar Badung, Denpasar-Bali) - Pebriani, Putu Fania; Kebayantini, Ni Luh Nyoman; Astika, Ketut Sudhana (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRACT Children who are labored as casual worker to carry their customerâ€™s goods on the head or â€œtukang suunâ€ at Badung market by their parents are considered as form of child exploitation because those children are labored without regarding to Labor Minister Rule No. 1 Year 1967 about children who are forced to work, boundaries of reasonableness, dan childrenâ€™s rights. The theory which was used in this research to analyze the problem was Social Interaction Theory (Superordination and Subordination) from Georg Simmel which was supported by his concepts about Individual Awareness and Culture Tragedy. This research used qualitative research method and applied descriptive and case study approach as the research type.Â  Collecting data is done by observation, deep interview, and study document techniques. The researchâ€™s result showed that the reasons of the presence of children as â€œtukang suunâ€ at Badung market are the low of parental education, poverty, individual encouragement, and the low of public understanding and awereness of the efforts to minimize children labor. Forms of children as â€œtukang suunâ€ exploitation can be seen from the childrenâ€™s age, work location, work time, the amount of wages, and violence. This exploitationâ€™s effects are those children do not have any chance to continue their study, bad mental and behavior of those children, and cleanliness less maintenance of children as â€œtukang suunâ€. Key Words : children as â€œtukang suunâ€, exploitation, Badung market